2015
DOI: 10.1007/s10909-015-1300-3
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Excitations in Confined Bose–Einstein Condensates, Searching for Quantum Turbulence

Abstract: We present a survey of macroscopic excitations of harmonically confined Bose-Einstein condensates (BEC), described by Gross-Pitaevskii (GP) equation, in search of routes to develop quantum turbulence. These excitations can all be created by phase imprinting techniques on an otherwise equilibrium BoseEinstein condensate. We analyze two crossed vortices, two parallel anti-vortices, a vortex ring, a vortex with topological charge Q = 2, and a tangle of 4 vortices. Since GP equation is time-reversal invariant, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Some of our cases, as mentioned above, have already been shown to be stable in [47]. Moreover, we also expect the topological defects to be quite stable, as shown in [53], where it is observed that non-stationary vortex states evolve in time, with the vortices precessing in the cloud, without dissipating into other structures. Finally, we discuss the feasibility of experimentally observing these defects.…”
Section: Final Commentssupporting
confidence: 65%
“…Some of our cases, as mentioned above, have already been shown to be stable in [47]. Moreover, we also expect the topological defects to be quite stable, as shown in [53], where it is observed that non-stationary vortex states evolve in time, with the vortices precessing in the cloud, without dissipating into other structures. Finally, we discuss the feasibility of experimentally observing these defects.…”
Section: Final Commentssupporting
confidence: 65%
“…(185). While this power-law behaviour has also emerged in numerical BEC simulations, 275,278 it has not yet been confirmed experimentally. Another feature of superfluid turbulence that has been recreated numerically is the non-classical distribution of the small-scale velocity field, which has already been detected in helium experiments.…”
Section: Turbulence and Instabilitiesmentioning
confidence: 97%
“…2.4 and 2.5) it results that in a trapped BEC Vinen ultraquantum turbulence is more likely to emerge. It has been recently demonstrated [44] that in the case of only two vortices initially in an orthogonal configuration, or even in the case of one doubly-charged vortex precessing and decaying in a spherically symmetric T = 0 trapped gas, there appear Kolmogorov-like spectra of the energy in the momentum space, but only over a wavenumber range of one decade. Numerical calculations based on the Gross-Pitaevskii equation [45] suggest that Kolmogorov scaling should emerge from the dynamics of vortices in a trapped Bose gas, but there is no experimental verification of the effect yet.…”
Section: Quantum Turbulencementioning
confidence: 99%